+0  
 
+1
54
1
avatar+428 

Find the center of -4x^2 + y^2 - 2y = 3.

waffles  Nov 20, 2017
Sort: 

1+0 Answers

 #1
avatar+79835 
+2

-4x^2 + y^2 - 2y  = 3

 

Rewrite as

 

y^2 -2y  - 4x^2  = 3     comlplete the square on y

 

y^2 - 2y + 1  -  4x^2  =  4       factor the frst three terms

 

(y - 1)^2   - 4x^2  = 4       divide through by 4

 

(y - 1)^2      -   x^2              

_______        ____         =      1

    4                  1

 

This is a "vertical" hyperbola.....the center is   (0, 1)

 

 

cool cool cool

CPhill  Nov 20, 2017

17 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details